2005
DOI: 10.1021/ol051151f
|View full text |Cite
|
Sign up to set email alerts
|

A New RNA Synthetic Method with a 2‘-O-(2-Cyanoethoxymethyl) Protecting Group

Abstract: A novel method for the synthesis of RNA oligomers with 2-cyanoethoxymethyl (CEM) as the 2'-hydroxyl protecting group has been developed. The new method allows the synthesis of oligoribonucleotides with an efficiency and final purity comparable to that obtained in DNA synthesis. [structure: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
68
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 20 publications
0
68
0
Order By: Relevance
“…To meet this need, we have developed an achiral 2′-hydroxyl protecting group, 2-cyanoethoxymethyl (CEM), that has low steric hindrance and that can be completely removed under mild conditions (25). CEM chemistry is also compatible with standard, unmodified DNA synthesizer equipment.…”
Section: Introductionmentioning
confidence: 99%
“…To meet this need, we have developed an achiral 2′-hydroxyl protecting group, 2-cyanoethoxymethyl (CEM), that has low steric hindrance and that can be completely removed under mild conditions (25). CEM chemistry is also compatible with standard, unmodified DNA synthesizer equipment.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] In this method, the CEM group is used as the 2′-hydroxyl protecting group. Because the CEM group is small, it offers minimal steric hindrance and so allows an increased yield at each coupling step.…”
Section: )mentioning
confidence: 99%
“…We turned our attention to a publication describing the novel (2-cyanoethoxy)methyl (CEM) 2 -O-protecting group for RNA synthesis. [6] They found that this group is readily removable upon treatment with tetrabutylammonium fluoride (TBAF) in dry tetrahydrofuran (THF). We asked the question if the mentioned group could be used for protection of the 3 -O-position in deoxynucleotides, and further, if the deprotection under such nonbiological conditions is possible without affecting the duplex structure of the DNA-template.…”
Section: Introductionmentioning
confidence: 99%